Hospitalizations for Varicella in children and adolescents in Portugal: 2000 to 2015 - Raquel Sofia da Silva Moreira (2020)
Objectives: Varicella is a common usually benign and auto-limited disease in children, but can lead to severe complications and hospitalization. With this study, we aim to analyze all varicella hospitalizations in order to provide epidemiological information to help outlining preventive policies. Design/Methods: We assessed all varicella hospitalizations in children from 0 to 17 years of age, from 2000 to 2015, in mainland public Portuguese hospitals, using a Portuguese administrative database. Seasonality, geographic distribution, severity, complications, risk factors and need of diagnostic and treatment procedures were analyzed by age groups. Results: A total of 5,120 hospitalizations were registered, with an annual rate of 17.2 hospitalizations/100,000 inhabitants. Higher number of hospitalizations occurred during the summer period and in Southern regions. The median length of stay was of four days. The main associated complications were impetigo, cellulitis and pneumonia. Of the total of patients, 0.8% were immunocompromised and 0.1% were pregnant. Total hospitalization costs during the 16-year period were estimated to be 7,110,718.70€. Discussion: This study showed similar results when compared to other European countries and provides useful epidemiological data to evaluate the relevance of including the Varicella Zoster Vaccine in our National Vaccination Program